The Role of Snail-1 in Thyroid Cancer—What We Know So Far - Wieczorek-Szukala, Katarzyna (J Clin Med, 2021)
Thyroid carcinomas, despite the usually indolent behaviour and relatively good overall prognosis, show a high tendency to gain invasive phenotype and metastasise in some cases. However, due to a relatively slow progression, the exact mechanisms governing the metastatic process of thyroid carcinomas, including the epithelial-to-mesenchymal transition (EMT), are poorly described. One of the best-known regulators of cancer invasiveness is Snail-1—a zinc-finger transcription factor that plays a key role as an EMT inducer. More and more attention is being paid to the role of Snail with regard to thyroid cancer development. Apart from the obvious implications in the EMT process, Snail-1 plays an important role in the regulation of chemoresistance of the thyroid cells and cancer stem cell (CSC) formation, and it also interacts with miRNA specific to the thyroid gland. The aim of this review was to summarise the knowledge on Snail-1, especially in the context of thyroid oncogenesis.